EVALUATION OF CO2, CH4, AND O3 GHGs FROM SATELLITES AGAINST GROUND-BASED MEASUREMENTS OVER SULAIMANI City, KR, IRAQ - Abdlrahman, W. J.; Najmaddin, P. M.; Majid, S. N. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was conducted from December 2021 to July 2022, except May 2022, and aimed to evaluate and validate CO2, CH4, and O3 GHGs in 13 different locations over Sulaimani city, Kurdistan Region-Iraq by means of remote sensing techniques from Sentinel 5 Precursor (S5P)/ TROPOMI and Orbiting Carbon Observatory-2 (OCO-2) satellites against ground-based measurements by using a  portable gases analyzer via three types of sensor heads, GSS  for the nominated gases of CO2, CH4, and O3. The Inverse Distance Weight (IDW) interpolation methods were used to map the CO2, CH4, and O3. The results of ground measurements showed high variability in some greenhouse gas concentration values and ranged between 285-508 ppm, 0-17000 ppb, and 0.25-64 ppb for CO2, CH4, and O3, respectively, in different locations and months. Satellite-predicted values for CO2, CH4, and O3 ranged between 416 - 418 ppm, 1858.99 - 1908.26, and 15.13 - 16.96 ppb, respectively, among the studied locations during the study periods. The RMSE ranged between 0.5 - 92.75 ppm, 99.11 – 2593.05 ppb, and 0.08 – 48.87 ppb for CO2, CH4, and O3, respectively.